Calcium-zinc heat stabilizer for rigid PVC foaming and preparation method thereof

CN122917399APending Publication Date: 2026-10-16JIAXING RUOTIAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611323129.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]针对上述现有技术存在的缺陷,本发明的目的在于,提供一种硬质PVC发泡用钙锌热稳定剂及其制备方法,旨在解决现有PVC硬质发泡板高白度和低比重无法平衡,及高吸湿的技术问题

Benefits of technology

本发明的钙锌热稳定剂通过在其中加入负载型的三元配合物功能填料,一方面利用锌离子作为催化活性中心,缩二脲配体协同活化AC发泡剂的分解位点,二者协同大幅提升催化效率,使AC发泡剂在加工过程中分解更完全,残留的黄色发泡剂显著减少,另一方面通过三元配位结构引入硬脂酸长链配体,利用长链烷基的疏水作用降低配合物自身的极性与吸水能力,并通过多孔载体的孔道负载与物理包覆作用,进一步隔绝外界水汽,使得最终得到的PVC发泡板同步实现白度大幅提升(b值≤11.5)与制品比重显著降低(密度<0.56g/cm3),钙锌热稳定剂的吸湿率显著降低(吸湿率<1.4%)。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a calcium-zinc heat stabilizer for rigid PVC foaming and a preparation method thereof. The calcium-zinc heat stabilizer comprises the following components: a supported functional filler, zinc stearate, calcium stearate, an antioxidant, a polyhydric alcohol ester auxiliary stabilizer and a lubricant. By adding the supported ternary complex functional filler into the calcium-zinc heat stabilizer, the obtained PVC foaming plate can realize the synchronous improvement of whiteness and the significant reduction of product specific gravity, and the moisture absorption rate of the calcium-zinc heat stabilizer is significantly reduced, so that the core performance requirements in the field of rigid PVC foaming plate can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of PVC heat stabilizer technology, specifically to a supported functional filler, and a calcium-zinc heat stabilizer for rigid PVC foam containing the functional filler and its preparation method. Background Technology

[0002] Rigid PVC foam boards, with their advantages of waterproofing, lightweight, acid and alkali resistance, thermal insulation, and sound insulation, are widely used in interior decoration, advertising display boards, building exterior wall decoration, and anti-corrosion engineering boards. Depending on the application, rigid PVC foam boards require products with different specific gravities. The lower the specific gravity, the higher the proportion of foaming agent required. This also results in a higher proportion of residual foaming agent during processing. Since yellow AC foaming agent is generally used, the relative whiteness of the final PVC foam board is lower, which affects the product's usability in applications requiring high-whiteness foam boards. Furthermore, as downstream applications increase their requirements for product appearance and performance, high whiteness and low specific gravity have become core performance requirements for high-end PVC foam boards.

[0003] Currently, the industry mainly relies on two approaches to improve whiteness: physical whitening and chemical foaming. Physical whitening is achieved by increasing the amount of titanium dioxide and fluorescent whitening agents, which significantly increases product cost and proportion. Chemical foaming improves whiteness by adding active components to catalyze the complete decomposition of AC foaming agents, reducing residual yellow foaming agents. In existing technologies, zinc salts and urea are common catalytic components of AC foaming agents, but the following technical problems still exist: ordinary zinc salts such as zinc stearate and zinc oxide have limited catalytic efficiency and insufficient improvement in whiteness; urea and biuret have better catalytic effects, but they are extremely hygroscopic, easily become damp and clump, cannot be directly added to solid calcium-zinc stabilizers, and have poor compatibility with PVC melt, making them prone to precipitation during processing.

[0004] Therefore, in view of the technical problems existing in the prior art, the development of a calcium-zinc heat stabilizer for rigid PVC foaming and its preparation method is of urgent industry demand and important industrial value. Summary of the Invention

[0005] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a calcium-zinc heat stabilizer for rigid PVC foam and its preparation method, which aims to solve the technical problems of the inability to balance high whiteness and low specific gravity of existing rigid PVC foam boards, as well as high moisture absorption.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a calcium-zinc heat stabilizer for rigid PVC foaming, comprising, by weight: Supported functional packing: 35~50 parts Zinc stearate: 15-25 parts Calcium stearate: 5-10 parts Antioxidant: 1-5 parts Polyol ester auxiliary stabilizer: 5-10 parts Lubricant: 5-10 parts.

[0007] Furthermore, the supported functional packing is a packing material supported on a biuret-stearic acid-zinc ternary complex; Furthermore, the supported functional packing uses a porous inorganic carrier as a skeleton, and loads the biuret-stearic acid-zinc ternary complex into the pores and surface of the carrier. Further, the molar ratio of biuret, stearic acid, and zinc ions in the biuret-stearic acid-zinc ternary complex is (0.8~1.2):(0.8~1.2):1, more preferably (0.9~1.1):(0.9~1.1):1, and most preferably 1:1:1; Furthermore, the porous inorganic carrier is selected from one or more of artificial zeolite, zinc-aluminum hydrotalcite, and porous nano-calcium carbonate; Furthermore, the preparation method of the supported functional filler includes the following steps: S1. Weigh out the zinc source, biuret and stearic acid in proportion, stir and dissolve them in an ethanol-water mixture to prepare a homogeneous ternary precursor mixture. S2. The porous inorganic carrier is added to the ternary precursor mixture in step S1 for impregnation treatment, so that the precursor can fully diffuse into the interior of the carrier pores. S3. Separate the carrier impregnated in step S2 and dry it to remove residual solvent; S4. The carrier dried in step S3 is reacted at a certain temperature for a certain time to allow the precursor to undergo an in-situ coordination reaction in the carrier pores. After the reaction is completed, the supported functional filler is obtained through post-treatment.

[0008] Preferably, in step S1, the zinc source is selected from one of zinc acetate dihydrate, anhydrous zinc acetate, active zinc oxide, and zinc stearate; the biuret is carbamoylurea; the molar ratio of biuret, stearic acid, and zinc ions is (0.8~1.2):(0.8~1.2):1, more preferably (0.9~1.1):(0.9~1.1):1, and most preferably 1:1:1; the total mass ratio of the biuret, stearic acid, and zinc source to the dry basis mass ratio of the porous inorganic carrier is (0.2~0.5):1, preferably (0.3~0.4):1; the volume ratio of ethanol to water is 1:1; and the stirring and dissolving temperature is 50~60℃. Preferably, in step S2, the impregnation conditions are: impregnation time 2~4h, stirring rate 100~200r / min; Preferably, in step S3, the separation method is vacuum filtration, and the drying conditions are: drying temperature 80~100℃, drying until the material has a constant weight; Preferably, in step S4, the temperature is 110~130℃, the reaction time is 1~2h; the post-treatment is to cool to room temperature and then crush and sieve, more preferably to sieve through a 200~300 mesh sieve.

[0009] Furthermore, the antioxidant is selected from one or two of antioxidant 1076 and antioxidant 168; Furthermore, the polyol ester auxiliary stabilizer is selected from one of trihydroxyethyl isocyanurate (THEIC) and pentaerythritol; Furthermore, the lubricant is selected from one or both of polyethylene wax or oxidized polyethylene wax.

[0010] Secondly, the present invention also provides a method for preparing a calcium-zinc heat stabilizer for rigid PVC foaming, specifically: weighing each component according to the weight parts, mixing them evenly, and discharging the material to obtain the calcium-zinc heat stabilizer. Furthermore, the mixing conditions are: high-speed mixer, rotation speed 1200~1500 r / min, time 20~30 min.

[0011] Compared with the prior art, the present invention has the following significant advantages: The calcium-zinc heat stabilizer of this invention incorporates a supported ternary complex functional filler. On one hand, it utilizes zinc ions as the catalytic active center, with biuret ligands synergistically activating the decomposition sites of the AC foaming agent. This synergistic effect significantly enhances catalytic efficiency, resulting in more complete decomposition of the AC foaming agent during processing and a substantial reduction in residual yellow foaming agent. On the other hand, the ternary coordination structure introduces long-chain stearic acid ligands, utilizing the hydrophobic effect of the long-chain alkyl group to reduce the polarity and water absorption capacity of the complex itself. Furthermore, the porous carrier's channel loading and physical coating further isolate external moisture, resulting in a significant increase in whiteness (b-value ≤ 11.5) and a significant reduction in specific gravity (density < 0.56 g / cm³) in the final PVC foamed board. 3 The moisture absorption rate of calcium-zinc heat stabilizer is significantly reduced (moisture absorption rate <1.4%). Detailed Implementation

[0012] Unless otherwise specified, the raw materials, equipment and methods used in this invention are all commonly used raw materials, equipment and conventional methods in the art; unless otherwise specified, the meanings of the terms in this specification are the same as those generally understood by those skilled in the art, but in case of conflict, the definitions in this specification shall prevail.

[0013] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Example 1

[0014] A calcium-zinc heat stabilizer for rigid PVC foaming, comprising: Supported functional packing: 50 parts Zinc stearate: 25 parts Calcium stearate: 5 parts Antioxidant 1076: 2 parts Trihydroxyethyl isocyanurate: 8 parts Polyethylene wax: 10 parts; Add the above components to a high-speed mixer and stir at 1500 r / min for 30 min. After mixing evenly, the product is discharged.

[0015] The supported functional filler was prepared by the following method: (1) Weigh 13.17 g of zinc acetate dihydrate, 6.19 g of biuret and 17.07 g of stearic acid (molar ratio of the three is 1:1:1), add ethanol-water mixed solvent (volume ratio 1:1) to make up to 200 mL, heat to 60 °C and stir until completely dissolved to obtain a ternary precursor mixture. (2) Add 100g of dry 4A artificial zeolite carrier to the above mixture, stir and soak at low speed of 100r / min at room temperature for 3h to allow the precursor to fully diffuse into the carrier pores and reach adsorption equilibrium. (3) The impregnated carrier is separated by vacuum filtration and dried in a 100°C forced-air oven until constant weight; (4) The dried carrier is heated to 120℃ and kept at that temperature for 2 hours to allow the adsorbed precursor to undergo a coordination reaction in situ within the carrier pores. After cooling, the carrier is crushed and passed through a 200-mesh sieve to obtain the supported functional filler. Example 2

[0016] A calcium-zinc heat stabilizer for rigid PVC foaming, comprising: Supported functional packing: 50 parts Zinc stearate: 25 parts Calcium stearate: 5 parts Antioxidant 1076: 2 parts Trihydroxyethyl isocyanurate: 8 parts Polyethylene wax: 10 parts; Add the above components to a high-speed mixer and stir at 1500 r / min for 30 min. After mixing evenly, the product is discharged.

[0017] The supported functional filler was prepared by the following method: (1) Weigh 16.46 g of zinc acetate dihydrate, 7.73 g of biuret and 21.34 g of stearic acid (molar ratio of the three is 1:1:1), add ethanol-water mixed solvent (volume ratio 1:1) to make up to 200 mL, heat to 60 °C and stir until completely dissolved to obtain a ternary precursor mixture. (2) Add 100g of dry zinc-aluminum hydrotalcite to the above mixture, stir and soak at low speed of 100r / min at room temperature for 3h to allow the precursor to fully diffuse into the carrier pores and reach adsorption equilibrium. (3) The impregnated carrier is separated by vacuum filtration and dried in a 100°C forced-air oven until constant weight; (4) The dried carrier is heated to 120℃ and kept at that temperature for 2 hours to allow the adsorbed precursor to undergo a coordination reaction in situ within the carrier pores. After cooling, the carrier is crushed and passed through a 200-mesh sieve to obtain the supported functional filler. Example 3

[0018] A calcium-zinc heat stabilizer for rigid PVC foaming, comprising: Supported functional packing: 50 parts Zinc stearate: 25 parts Calcium stearate: 5 parts Antioxidant 1076: 2 parts Trihydroxyethyl isocyanurate: 8 parts Polyethylene wax: 10 parts; Add the above components to a high-speed mixer and stir at 1500 r / min for 30 min. After mixing evenly, the product is discharged.

[0019] The supported functional filler was prepared by the following method: (1) Weigh 13.17 g of zinc acetate dihydrate, 4.95 g of biuret, and 13.66 g of stearic acid (the molar ratio of biuret, stearic acid, and zinc ions is 0.8:0.8:1), add ethanol-water mixed solvent (volume ratio 1:1) to a final volume of 200 mL, heat to 60 °C and stir until completely dissolved to obtain a ternary precursor mixture; (2) Add 100g of dry 4A artificial zeolite carrier to the above mixture, stir and soak at low speed of 100r / min at room temperature for 3h to allow the precursor to fully diffuse into the carrier pores and reach adsorption equilibrium. (3) The impregnated carrier is separated by vacuum filtration and dried in a 100°C forced-air oven until constant weight; (4) The dried carrier is heated to 120℃ and kept at that temperature for 2 hours to allow the adsorbed precursor to undergo a coordination reaction in situ within the carrier pores. After cooling, the carrier is crushed and passed through a 200-mesh sieve to obtain the supported functional filler. Example 4

[0020] A calcium-zinc heat stabilizer for rigid PVC foaming, comprising: Supported functional packing: 50 parts Zinc stearate: 25 parts Calcium stearate: 5 parts Antioxidant 1076: 2 parts Trihydroxyethyl isocyanurate: 8 parts Polyethylene wax: 10 parts; Add the above components to a high-speed mixer and stir at 1500 r / min for 30 min. After mixing evenly, the product is discharged.

[0021] The supported functional filler was prepared by the following method: (1) Weigh 13.17 g of zinc acetate dihydrate, 7.43 g of biuret, and 20.48 g of stearic acid (the molar ratio of biuret, stearic acid, and zinc ions is 1.2:1.2:1), add ethanol-water mixed solvent (volume ratio 1:1) to a final volume of 200 mL, heat to 60 °C and stir until completely dissolved to obtain a ternary precursor mixture; (2) Add 100g of dry 4A artificial zeolite carrier to the above mixture, stir and soak at low speed of 100r / min at room temperature for 3h to allow the precursor to fully diffuse into the carrier pores and reach adsorption equilibrium. (3) The impregnated carrier is separated by vacuum filtration and dried in a 100°C forced-air oven until constant weight; (4) The dried carrier is heated to 120℃ and kept at that temperature for 2 hours to allow the adsorbed precursor to undergo a coordination reaction in situ within the carrier pores. After cooling, the carrier is crushed and passed through a 200-mesh sieve to obtain the supported functional filler.

[0022] Comparative Example 1 A calcium-zinc heat stabilizer for rigid PVC foaming, comprising: Artificial zeolite: 50 parts Zinc stearate: 25 parts Calcium stearate: 5 parts Antioxidant 1076: 2 parts Trihydroxyethyl isocyanurate: 8 parts Polyethylene wax: 10 parts; Add the above components to a high-speed mixer and stir at 1500 r / min for 30 min. After mixing evenly, the product is discharged.

[0023] Comparative Example 2 A calcium-zinc heat stabilizer for rigid PVC foaming, comprising: Non-loaded functional packing: 50 parts Zinc stearate: 25 parts Calcium stearate: 5 parts Antioxidant 1076: 2 parts Trihydroxyethyl isocyanurate: 8 parts Polyethylene wax: 10 parts; Add the above components to a high-speed mixer and stir at 1500 r / min for 30 min. After mixing evenly, the product is discharged.

[0024] The unloaded functional filler was prepared according to the following method: (1) Weigh 13.17 g of zinc acetate dihydrate, 6.19 g of biuret and 17.07 g of stearic acid (molar ratio of the three is 1:1:1), add ethanol-water mixed solvent (volume ratio 1:1) to make up to 200 mL, heat to 60 °C and stir until completely dissolved to obtain a ternary precursor mixture. (2) The above ternary precursor mixture was heated to 85°C and stirred under reflux for 2 hours to allow the three components to fully coordinate and generate a ternary complex precipitate. (3) After the reaction is completed, cool to room temperature, filter to separate the solid product, wash 3 times with anhydrous ethanol, dry in a 100℃ oven to constant weight, pulverize and pass through a 200-mesh sieve to obtain ternary complex powder. (4) Take 100g of dry 4A artificial zeolite and mix it with the above ternary complex powder at room temperature to obtain a mixed filler, which is a non-loaded functional filler.

[0025] Comparative Example 3 A calcium-zinc heat stabilizer for rigid PVC foaming, comprising: Binary supported functional packing: 50 parts Zinc stearate: 25 parts Calcium stearate: 5 parts Antioxidant 1076: 2 parts Trihydroxyethyl isocyanurate: 8 parts Polyethylene wax: 10 parts; Add the above components to a high-speed mixer and stir at 1500 r / min for 30 min. After mixing evenly, the product is discharged.

[0026] The binary supported functional filler was prepared according to the following method: (1) Weigh 13.17 g of zinc acetate dihydrate and 6.19 g of biuret (molar ratio of the two is 1:1), add ethanol-water mixed solvent (volume ratio 1:1) to make up to 200 mL, heat to 60 °C and stir until completely dissolved to obtain a binary precursor mixture. (2) Add 100g of dry 4A artificial zeolite carrier to the above mixture, stir and soak at low speed of 100r / min at room temperature for 3h to allow the precursor to fully diffuse into the carrier pores and reach adsorption equilibrium. (3) The impregnated carrier is separated by vacuum filtration and dried in a 100°C forced-air oven until constant weight; (4) The dried carrier is heated to 120°C and kept at that temperature for 2 hours to allow the adsorbed precursor to undergo in-situ coordination reaction in the carrier pores. After cooling, the carrier is crushed and passed through a 200-mesh sieve to obtain a binary supported functional filler.

[0027] Comparative Example 4 A calcium-zinc heat stabilizer for rigid PVC foaming, the difference being that: 13.17g of zinc acetate dihydrate, 4.33g of biuret, and 11.95g of stearic acid are weighed (the molar ratio of biuret, stearic acid, and zinc ions is 0.7:0.7:1), while the rest remains the same as in Example 1.

[0028] Comparative Example 5 A calcium-zinc heat stabilizer for rigid PVC foaming, the difference being that: 13.17g of zinc acetate dihydrate, 8.05g of biuret, and 22.09g of stearic acid are weighed (the molar ratio of biuret, stearic acid, and zinc ions is 1.3:1.3:1), while the rest remains the same as in Example 1.

[0029] Performance testing: The calcium-zinc heat stabilizers of Examples 1-4 and Comparative Examples 1-5 were used to prepare rigid PVC foam materials, specifically as follows: The rigid PVC foam material has the following formula (parts by weight): 100 parts PVC resin (SG-8 type), 25 parts heavy calcium carbonate, 2 parts CPE (135A type), 1 part ACR (401 type), 1 part titanium dioxide, 0.8 parts AC foaming agent, 0.4 parts sodium bicarbonate, 5 parts 530 type PVC foaming regulator, and 4 parts calcium-zinc heat stabilizer as described in the examples or comparative examples. Processing technology: The components of the above formula are mixed at high speed and discharged. The mixture is then extruded and granulated using a twin-screw extruder, and injection molded to prepare standard samples of 100mm×20mm×3mm.

[0030] Whiteness test: The b value of the sample is measured using a colorimeter. The lower the b value, the lower the yellowness of the sample and the higher the whiteness of the product. Specific gravity test: The density of the foamed sample was tested using the displacement method; Moisture absorption performance test: The moisture absorption rate of the stabilizer was tested according to Clause 4.6 of GB / T 16913-2008. The test conditions were 25℃, relative humidity 70%, and placement for 48 hours. The test data are shown in Table 1:

[0031] Comparing the test results of Examples 1-4 and Comparative Examples 1-5 in Table 1, it can be seen that the calcium-zinc heat stabilizer of the present invention, by adding a supported ternary complex functional filler, ultimately achieves a significant increase in whiteness (b-value ≤ 11.5) and a significant decrease in specific gravity (density < 0.56 g / cm³) in the final PVC foam board. 3 The moisture absorption rate of calcium-zinc heat stabilizer is significantly reduced (moisture absorption rate <1.4%).

[0032] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A calcium-zinc heat stabilizer for rigid PVC foaming, characterized in that, Its components, by weight, include: Supported functional packing: 35~50 parts Zinc stearate: 15-25 parts Calcium stearate: 5-10 parts Antioxidant: 1-5 parts Polyol ester auxiliary stabilizer: 5-10 parts Lubricant: 5-10 parts; The loaded functional packing is a packing material loaded with a biuret-stearic acid-zinc ternary complex.

2. The calcium-zinc heat stabilizer according to claim 1, characterized in that, The supported functional packing uses a porous inorganic carrier as a skeleton, and loads the biuret-stearic acid-zinc ternary complex into the pores and surface of the carrier.

3. The calcium-zinc heat stabilizer according to claim 1, characterized in that, The molar ratio of biuret, stearic acid and zinc ions in the biuret-stearic acid-zinc ternary complex is (0.8~1.2):(0.8~1.2):1; the porous inorganic carrier is selected from one or more of artificial zeolite, zinc-aluminum hydrotalcite and porous nano calcium carbonate.

4. The calcium-zinc heat stabilizer according to claim 1, characterized in that, The preparation method of the supported functional filler includes the following steps: S1. Weigh out the zinc source, biuret and stearic acid in proportion, stir and dissolve them in an ethanol-water mixture to prepare a homogeneous ternary precursor mixture. S2. The porous inorganic carrier is added to the ternary precursor mixture in step S1 for impregnation treatment, so that the precursor can fully diffuse into the interior of the carrier pores. S3. Separate the carrier impregnated in step S2 and dry it to remove residual solvent; S4. The carrier dried in step S3 is reacted at a certain temperature for a certain time to allow the precursor to undergo an in-situ coordination reaction in the carrier pores. After the reaction is completed, the supported functional filler is obtained through post-treatment.

5. The calcium-zinc heat stabilizer according to claim 4, characterized in that, In step S1, the zinc source is selected from one of zinc acetate dihydrate, anhydrous zinc acetate, active zinc oxide, and zinc stearate; the biuret is carbamoylurea; the molar ratio of biuret, stearic acid, and zinc ions is (0.8~1.2):(0.8~1.2):1; the ratio of the total mass of biuret, stearic acid, and zinc source to the dry basis mass of the porous inorganic carrier is (0.2~0.5):1; the volume ratio of ethanol to water is 1:1; and the stirring and dissolving temperature is 50~60℃. In step S2, the impregnation conditions are: impregnation time 2~4h, stirring rate 100~200r / min; In step S3, the separation method is vacuum filtration, and the drying conditions are: drying temperature 80~100℃, drying until the material has a constant weight; In step S4, the temperature is 110~130℃, the reaction time is 1~2h; the post-treatment is to cool to room temperature and then crush and sieve, more preferably to sieve through a 200~300 mesh sieve.

6. The calcium-zinc heat stabilizer according to claim 1, characterized in that, The antioxidant is selected from one or two of antioxidant 1076 and antioxidant 168; the polyol ester auxiliary stabilizer is selected from one of trihydroxyethyl isocyanurate (THEIC) and pentaerythritol; the lubricant is selected from one or two of polyethylene wax or oxidized polyethylene wax.

7. The method for preparing the calcium-zinc heat stabilizer for rigid PVC foaming according to any one of claims 1 to 6, characterized in that, Weigh each component according to the weight percentage, mix them evenly, and discharge to obtain the calcium-zinc heat stabilizer.

8. The method for preparing the calcium-zinc heat stabilizer according to claim 7, characterized in that, The mixing conditions are: high-speed mixer, rotation speed 1200~1500 r / min, time 20~30 min.